Drosophila: Retrotransposons Making up Telomeres - Elena Casacuberta (Viruses, 2017)
Drosophila and extant species are the best-studied telomerase exception. In this organism, telomere elongation is coupled with targeted retrotransposition of Healing Transposon (HeT-A) and Telomere Associated Retrotransposon (TART) with sporadic additions of Telomere Associated and HeT-A Related (TAHRE), all three specialized non-Long Terminal Repeat (non-LTR) retrotransposons. These three very special retroelements transpose in head to tail arrays, always in the same orientation at the end of the chromosomes but never in interior locations. Apparently, retrotransposon and telomerase telomeres might seem very different, but a detailed view of their mechanisms reveals similarities explaining how the loss of telomerase in a Drosophila ancestor could successfully have been replaced by the telomere retrotransposons. In this review, we will discover that although HeT-A, TART, and TAHRE are still the only examples to date where their targeted transposition is perfectly tamed into the telomere biology of Drosophila, there are other examples of retrotransposons that manage to successfully integrate inside and at the end of telomeres. Because the aim of this special issue is viral integration at telomeres, understanding the base of the telomerase exceptions will help to obtain clues on similar strategies that mobile elements and viruses could have acquired in order to ensure their survival in the host genome.